MATA KULIAH PANCASILA DALAM MEMBANGUN SIKAP MODERASI BERAGAMA MAHASISWA DI ERA DIGITAL: STUDI KASUS PADA DI STAI DR KHEZ MUTTAQIEN PURWAKARTA - Purnamasari, Rika; Maftuh, Bunyamin; Hidayat, Mupid; Isya, Warlim; Nurdin, Encep Syarief; Widiniani, Santy (Jurnal Visi Ilmu Pendidikan, 2026)
Pancasila education plays a strategic role in shaping national character and instilling the values of religious moderation in students, particularly at Islamic religious universities. This study aims to examine the implementation of Pancasila courses in developing religious moderation among students at STAI DR. KHEZ Muttaqien Purwakarta and assess its contribution to the formation of moderate, inclusive, and nationally-minded religious character. The research method used a qualitative approach with a case study design. The research informants consisted of four Pancasila lecturers and eight students selected through purposive sampling. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis included data reduction, data presentation, and conclusion drawing. The results show that Pancasila learning is systematically integrated with the concept of religious moderation through curriculum planning, CPMK development, collaborative methods, digital case study analysis, and an inclusive campus culture.